Magazines and modernity in Brazil: Transnationalisms and cross-cultural exchanges - Correa, Felipe Botelho; dos Santos Guimarães, Valéria [UNESP]; Velloso, Monica Pimenta (My University, 2020)
The essays gathered in Magazines and Modernity in Brazil explore transnational topics such as architecture; cosmopolitanism and universalism; antisemitism, anti-war movements; visual artistic movements; advertising; anti-racism; avant-garde; class; consumer society; design; ethnicity and race; fascism and anti-fascism; intellectual elites; literature; modernity; publishing; translation, as well as book and periodical exchange, which is the main focus of this collection. Together, these essays propose a critique of traditional comparatist approaches, promoting instead the study of contact zones and intersections, highlighting the place of production and reception of cultural products, as well as the role of mediators. What guide these analyses of magazines are concepts such as connected and shared histories, which emphasize transnational interactions. Within the spectrum of global history, this collection is related to a recent body scholarship on cultural transfers, which opened a fertile field for new research based on the analysis of transnational movements not only of ideas but also of networks and magazines. Organized chronologically, the chapters explore a period from the mid-nineteenth century to the aftermath of World War II, always having key magazines as the focus of analysis. The authors deliberately move away from traditional comparative approaches, in which two or more nations are set as a parameter, leading to emphasize their similarities and differences in a rigid framework that does not take into account interactions and cross-pollination of cultures and ideas. Some of the keywords that appear here are transnational models, global, circulation, mediation, hybridity, mestizaje, as well as histories that are shared and connected. These keywords help the authors to analyse the formation and development of the participation of Brazil in the global, modern periodical print culture. However, it should be noted that the purpose of this book is not to suggest a supposed singularity of the Brazilian case. The contribution of this volume of essays is precisely the opposite of this, showing how modernity in Brazil, including what is conventionally called modernism, is a complex expression of transnational movements and cross-cultural exchanges.